For the want of a nail: the Western Allies quest to synchronize maneuver and logistics during operations Torch and Overlord - Mullins, Jeffrey Bryan (Kansas State University, 2020)
Understanding why the Western Allies failed to penetrate the western border of Germany in the fall of 1944 is a longer and more involved story than most histories of the topic imply. Allied performance in the European Theater of Operations during World War II is directly linked to their performance in the Mediterranean Theater of Operations (MTO) and before that, in the North African theater. This study focuses on how the Western Allies conducted campaigns – how they ran combined headquarters in order to plan and supervise joint, theater-level operations, and how those activities changed over time as the key leaders involved gained combat experience. After looking at the efforts of the Allied over this longer window of time, a new conclusion about why the pursuit phase of Overlord failed to penetrate the Westwall becomes clear. LTG J. C. H. Lee’s Communication’s Zone (COMZ) was unprepared to fulfill the logistical requirements of the Allied fall campaign in France in 1944, contributing directly to disappointment over the outcome of the campaign. For those who expected two years of combat experience to result in more effective performance in subsequent action, the failure was surely surprising. This study examines why COMZ could not manage the theater’s logistics and distribution system, and how Supreme Headquarters, Allied Expeditionary Force (SHAEF) failed to correct this shortcoming as it sought to synchronize joint operations with logistical requirements and the limitations they imposed. By contrasting the operational methods used by the United States (U.S.) and United Kingdom (U.K). and by looking at how Torch and Overlord unfolded, this study reaches three conclusions. First, COMZ was woefully unprepared to execute its combat mission in August 1944, and its failures lengthened the war considerably. Second, this failure was directly linked to the U.S. Army’s inability to integrate lessons learned at European Theater of Operations, U.S. Army (ETOUSA). Third, the work demonstrates how critical the integration of maneuver and sustainment is at the operational level of war and how U.S. doctrine and practice predating the war made this difficult to recognize. Finally, successful command at the theater and operational level relies upon consensus and cooperation, unlike the more directive nature of tactical control. COMZ and SHAEF were not prepared to fulfil their roles in August and September because the U.S. experience in World War One and the doctrine that emerged from that experience resulted in the adoption of a model for theater command that was eventually rejected in 1944. Although useful lessons were gained during Torch and implemented at Allied Force Headquarters (AFHQ), ETOUSA and Lee’s Service of Supply (SOS) did not integrate them. Those lessons were obscured when key personalities rotated or the org chart changed -- it took time for AFHQ, North African Theater of Operations, U.S. Army (NATOUSA), and the functional components to gel. ETOUSA and SOS faced different challenges, were busy with Bolero, and suffered through personnel turnover and restrictions of their own. A final round of reorganization swept through the U.K. over the winter of 1943 and 1944 when much of the command team relocated from the MTO to London. These organizational changes left in question who exactly was in charge of the various aspects of the sustainment mission during Overlord. Lee proved less effective than his peers when it came to producing results that were valued by the operational commands, and SHAEF and the army groups gradually poached ownership of planning and integrating logistical support from SOS/COMZ as a result. Lee held on to running the communications zone in France, but then he did not properly prepare for the mission. By the time SHAEF realized COMZ did not know how to do its job, it was too late to save the fall campaign. Just how bad things had gotten by October and November was masked by poor recordkeeping during the pursuit, confusion over what was really happening within the subordinate commands, and a narrative advanced by Eisenhower in January 1945 designed to paint a more flattering picture of recent events. Eisenhower manipulated facts in a report submitted to the Combined Chiefs of Staff in order to justify his decisions in France, dismiss any reported “mistakes” made during the fall, and ensure he retained personal control over the three army groups rather than reappointing a subordinate overall ground commander. In the process, Eisenhower initiated the cover-up that would make it so difficult to establish why the pursuit broke down.
Keywords: World War II; U.S. Army; Logistics; SHAEF; AFHQ; Operational art; ETOUSA; Combined headquarters; Joint headquarters